A Simulation Study of the Response of Plant-type and Nitrogen Fertilization on the Grain Yield of Pearl Millet - O Leary, G J; Joshi, N L; Oosterom, E J Van (Annals of Arid Zone, 2016)
A simulation study was made on the response of plant-type and nitrogen fertilization on the yield of pearl millet in Rajasthan, India. A model of the pearl millet crop (APSIM-Millet) was tested against experimental and district data and was shown to be responsive to applied nitrogen (Root Mean Square Error=230 kg haÂ·l , 13%) and to varied weather conditions with and without applied nitrogen in the region. The simulation study employed both observed (14-34 years between 1963 and 1997) and synthetic (50 years) daily weather data in a comparative analysis that showed little difference in conclusions if either data sequence were used. The probability analyses showed a strong plant-type, nitrogen and site effect in response to variation in weather (observed or synthetic). At Pali and Jodhpur choice of cultivar made a large yield difference with a strong interaction with nitrogen. In terms of median res onse, highest yield was achieved with cultivar RCB-IC911 (median 800 kg ha-) followed by cultivar HHB67 (median 613 kg haÂ·l ) with the lowest consistent yield from cultivar WRajPop (median 500 kg ha’ At Bikaner and Jaisalmer cultivar response was much smaller than at the wetter sites but generally the same order of response was seen. Similarly, the response to nitrogen was greatest at Pali and Jodhpur; moreover, the nitrogen response was generally larger than the cultivar response, despite the’ negative effect in dry conditions at Pali. Thus, at these wetter sites significant yield increases (e.g. 700-900 kg haÂ·1 ) above what is currently achieved with unfertilized landraces are likely with the combination of an improved cultivar and application of N fertilizer. Even at the drier site at Bikaner, yields could be more than doubled (from 250 to 550 kg haÂ·l ) with improved cultivars and N-fertilization. However, at Jaisalmer, improved cultivars and N-fertilization could not be economically justified. Significant benefits are likely from an integrated approach to plant breeding and agronomy in these semi-arid regions of India and Africa where N deficiency is endemic. Key words: Arid region, grain yield, nitrogen, pearl millet, plant-type, simulation.